2018
DOI: 10.1016/j.schres.2018.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of falls and fractures leading to hospitalization in people with schizophrenia spectrum disorder: A large representative cohort study

Abstract: Comorbid physical health conditions and analgesic medication prescription were associated with higher risk of falls and fractures. Osteoporosis and previous fracture were strong predictors for subsequent fractures. Interventions targeting bone health and falls/fractures need to be developed and evaluated in these populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
18
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 46 publications
5
18
0
1
Order By: Relevance
“…The cohort included all individuals aged 18 years or older with a diagnosis of SSD (ICD-10: F20-F29) and had at least one face to face contact with SLaM during the period between 1 st January 2011 and 31 st December 2012, and who were alive on 1 st January 2013 (set up in this way to allow all cases to have at least 5 year follow-up). In recognition of the heterogeneous nature of schizophrenia, we included the spectrum of schizophrenia (SSD) as in accordance with previous research papers (Chang et al, 2010;Stubbs, Mueller, et al, 2018). We used primary and secondary diagnoses of F20-29 within the structured ICD-10 codes that were recorded routinely in the source EHR.…”
Section: Study Populationmentioning
confidence: 99%
“…The cohort included all individuals aged 18 years or older with a diagnosis of SSD (ICD-10: F20-F29) and had at least one face to face contact with SLaM during the period between 1 st January 2011 and 31 st December 2012, and who were alive on 1 st January 2013 (set up in this way to allow all cases to have at least 5 year follow-up). In recognition of the heterogeneous nature of schizophrenia, we included the spectrum of schizophrenia (SSD) as in accordance with previous research papers (Chang et al, 2010;Stubbs, Mueller, et al, 2018). We used primary and secondary diagnoses of F20-29 within the structured ICD-10 codes that were recorded routinely in the source EHR.…”
Section: Study Populationmentioning
confidence: 99%
“…33,34 Falls risk in latelife psychotic disorders has received very little investigation, although recent cohort studies have suggested that this population is at increased risk of fractures. 35,36 A recent systematic review suggested that people with depressive symptoms are at increased risk of hip fractures, although relatively few (n ¼ 5) studies included people with confirmed depression. 37 A meta-analysis suggested that people with major depression were at increased risk of future falls, but the sample size was small (n ¼ 965).…”
mentioning
confidence: 99%
“…Las condiciones patológicas que alteran el pensamiento prolongan la estadía de los pacientes (8)(9)(10)(11)21); en este sentido, en el presente estudio, una estancia mayor a 8 días s identificó como un factor que aumenta el riesgo de caídas (OR=4.51 (3.23-6.30)). Estas condiciones requieren como parte de su manejo la implementaciones de medidas de sujeción y sedación del paciente, las cuales también aumentan el riesgo de caídas que estos medicamentos pueden provocar efectos extrapiramidales y, e consecuencia, propiciar el evento caída (11).…”
Section: Discusión [T1]unclassified